Cardiac Lymphoma Revealed by Atrial Mass - Sawadogo, Adama; Miguel, Bruno; Azarnoush, Kasra; Camilleri, Lionel (Cardiovascular Journal, 2018)
Primary cardiac lymphoma (PCL) represents a very exceptional clinical entity whose treatment is based on chemotherapy. In this case report, the authors highlight the key role of cardiac surgery in the diagnosis of PCL in a 66-year-old female patient. She was given chemotherapy and so far was on remission. Cardiovasc. j. 2018; 11(1): 86-88